Constraints on the jumping and prey-capture abilities of ant-mimicking spiders (Salticidae, Salticinae, Myrmarachne) - Hashimoto, Yoshiaki (Sci Rep, 2020)
Accurate morphological ant mimicry by Myrmarachne jumping spiders confers strong protective benefits against predators. However, it has been hypothesized that the slender and constricted ant-like appearance imposes costs on the hunting ability because their jumping power to capture prey is obtained from hydraulic pressure in their bodies. This hypothesis remains to be sufficiently investigated. We compared the jumping and prey-capture abilities of seven Myrmarachne species and non-myrmecomorphic salticids collected from tropical forests in Malaysian Borneo and northeastern Thailand. We found that the mimics had significantly reduced abilities compared with the non-mimics. The analysis using geometric morphometric techniques revealed that the reduced abilities were strongly associated with the morphological traits for ant mimicry and relatively lower abilities were found in Myrmarachne species with a more narrowed form. These results support the hypothesis that the jumping ability to capture prey is constrained by the morphological mimicry and provide a new insight into understanding the evolutionary costs of accurate mimicry.